Pengaruh Penambahan Produk Fermentasi Air Kelapa Pada Sari Buah Belimbing (Averrhoa carambola L.) Terhadap Sifat Mikrobiologis Dan Tingkat Penerimaan Konsumen - Junia, Ayu Astian; Rukmini, Ambar; Darmawan, Eman; Laswati, Dyah Titin (AGROTECH : JURNAL ILMIAH TEKNOLOGI PERTANIAN, 2024)
This research aims to determine the effect of adding a fermented coconut water produc on the microbiological, organoleptic properties of star fruit juice, and chemical properties (pH). This research used a Completely Randomized Design method, the effect of adding Biojanna (0%, 2%, 4%, 6%) to the star fruit juice produced was analyzed microbiologically (TPC Bacteria and TPC Lactic Acid Bacteria. ) two repetitions, chemical analysis measurements (pH), t-test carried out 3 times and organoleptic tests using the Hedonic method (aroma, taste and overall preference). Observed data for each parameter was statistically analyzed using ANOVA and continued with Duncan's New Multiple Range Test (DNMRT) at a significance level of 5% if there is a significant difference. The research results show that Biojanna products do not contain lactic acid bacteria (0%, 2%, 4%, 6%) in the juice Star fruit has no significant effect on microbiological and organoleptic properties. The addition of Biojanna to star fruit juice has no impact on the addition of bacteria, and has no effect on consumer acceptance in terms of (taste, aroma, and overall preference) adding 2% Biojanna to the juice fruit is the sample preferred by panelists, with the maximum contamination limit (ALT) before storage in the refrigerator, the value is 6.9 x 103 CFU/ml, and after storage, the value is 1.9 x 104 CFU/ml, the pH value before storage is 5, 96, and after storing the pH value of 6.09.